Principais Aspectos da Promoção de Direitos Humanos na Organização dos Estados Americanos - Carvalho Ramos, André (Hemisferio - Revista del Colegio Interamericano de Defensa, 2017)
This article tries to analyze in great detail the main aspects connected to the human rights protection system, based on the OAS Charter, and its main characteristics.